The formation mechanism and generation conditions of urban residents' public safety behavior. Issue 1 (26th January 2023) - Cheng, Yun; Yin, Jie; Huang, Paoyu; Ni, Yensen
Abstract: The formation mechanism and generation condition configuration of urban residents' public safety behavior crucial for reducing urban public safety accidents were identified using the structural equation model (SEM) and the fsQCA method to analyze 465 survey samples. The findings showed that organizational safety communication, community safety support, family safety climate, safety consciousness, and safety motivation are driving factors influencing individual safety behavior and that residents' safety behavior is positively influenced by emotional safety culture. Furthermore, nine generational configurations of these antecedent variables are sufficient to explain the emergence of high levels of safety behavior. Because most previous research has focused on the linear effects of single or multiple factors on outcome variables while ignoring "combined effects, " this study employed fsQCA to identify "combined effects" among antecedent factors of safety behavior from multiple perspectives. The results revealed that no single factor, but rather a combination of factors, led to high levels of safety behavior, shedding light on the importance of "combined effects" among variables and providing theoretical and practical insights into urban residents' public safety behavior.